Establishment and characterization of a brain‐cell line from kelp grouper Epinephelus moara. Issue 2 (14th January 2018) - Liu, X. F.; Wu, Y. H.; Wei, S. N.; Wang, N.; Li, Y. Z.; Zhang, N. W.; Li, P. F.; Qin, Q. W.; Chen, S. L.
Abstract : A new brain‐cell line, EMB, was developed from kelp grouper Epinephelus moara, a cultured marine fish. The EMB cells were subcultured for more than 60 passages. The cells were cultured in Leibovitz's L‐15 medium (L15) supplemented with antibiotics, foetal bovine serum (FBS), 2‐mercaptoethanol (2‐ME) and basic fibroblast growth factor (bFGF). The cells could grow at 18–30° C, with the maximum growth between 24 and 30° C. The optimum FBS concentration for the cells growth ranged between 15 and 20%. Chromosome analysis indicated that the modal chromosome number was 48 in the cells at passage 45. After being transfected with pEGFP‐N3 plasmid, the cells could successfully express green fluorescence protein (GFP), implying that this cell line can be used for transgenic studies. A significant cytopathic effect (CPE) was observed in the cells after infection with Singapore grouper iridovirus (SGIV) or red spotted grouper nervous necrosis virus (RGNNV) and the viral replication was confirmed by quantitative real‐time PCR (qrt‐PCR) assay, which suggested EMB's application potential for studies of SGIV and RGNNV.